IMPLEMENTASI PELAYANAN PUBLIK MELALUI E-GOVERNMENT DI DINAS SOSIAL KABUPATEN GORONTALO - Pakudu, Robin (Jurnal Administrasi Negara dan Ilmu Pemerintahan, 2024)
This study aims to determine the extent of the Implementation of Public Services through the Gorontalo District Social Service E-Government. Descriptive research method using qualitative. E-Government applications can facilitate government services to the community, especially in the SIKS-NG application, which is an application regarding social assistance. This can be supported by four indicators, namely the availability of information in data and information centers, the availability of information for promotional needs, the availability of E-Government applications to support office work and public services, the availability of public dialogue applications to improve communication between the public sector and society through SMS applications. , E-mail, Teleforence. In this case it can be concluded that the Implementation of Public Services through E-Government in the Gorontalo Regency Social Service can be seen from four indicators that are quite good, namely in increasing public dialogue communication between the public sectors.